Mechanical and thermal properties of polypropylene/clay roof tiles waste (PP/CRTW) composites - Tuah, Siti Nor Aizura (2015)
The usage of clay roof tiles waste as a filler in composite was studied. Polypropylene (PP) composites of clay roof tiles wastes (CRTW) for low strength applications were prepared at filler contents 5%, 10%, 15%, 20%, 25% and 30%. Unfilled PP used as reference sample. The clay roof tiles wastes were prepared to achieve 45 micron in size to mix with PP. The composites were mixed using double hot roll mill mixer at temperature 190°C. The final products of the composites prepared were in a granul form which undergone granulation process after mixing. Injection moulding process also conducted to get the composites in dumbbell shape. The mechanical and thermal properties of the composites prepared were determined. Results showed that the CRTW improved the hardness properties and melt density with the increases in the filler content. On the other hand melt flow index was however observed to decrease with increases in the filler content. For the thermal properties at maximum loading of filler content it shows the maximum temperature of weight loss rate, Tpeak and the onset decomposition temperature, Tonset higher compared to unfilled PP. The tensile properties for ultimate tensile strength, elongation at break, break strain percentage, maximum load and toughness were however also observed to decrease with increases in the filler content. FTIR results showed the main functional group of PP as a dominant constituent in PP/CRTW composites still remained at the wave number around 2917~2950 cm-1 at all filler content.